Current and future trends in socio-economic, demographic and governance factors affecting global primate conservation - Estrada, Alejandro; Garber, Paul A.; Chaudhary, Abhishek (PeerJ, 2020)
Currently, 65% of extant primate species (ca 512 species) distributed in 91 countries in the Neotropics, mainland Africa, Madagascar, South Asia and Southeast Asia are threatened with extinction and 75% have declining populations as a result of deforestation and habitat loss resulting from increasing global market demands, and land conversion for industrial agriculture, cattle production and natural resource extraction. Other pressures that negatively impact primates are unsustainable bushmeat hunting, the illegal trade of primates as pets and as body parts, expanding road networks in previously isolated areas, zoonotic disease transmission and climate change. Here we examine current and future trends in several socio-economic factors directly or indirectly affecting primates to further our understanding of the interdependent relationship between human well-being, sustainable development, and primate population persistence. We found that between 2001 and 2018 ca 191 Mha of tropical forest (30% canopy cover) were lost as a result of human activities in the five primate range regions. Forty-six percent of this loss was in the Neotropics (Mexico, Central and South America), 30% in Southeast Asia, 21% in mainland Africa, 2% in Madagascar and 1% in South Asia. Countries with the greatest losses (ca 57% of total tree cover loss) were Brazil, Indonesia, DRC, China, and Malaysia. Together these countries harbor almost 50% of all extant primate species. In 2018, the world human population was estimated at ca 8bn people, ca 60% of which were found in primate range countries. Projections to 2050 and to 2100 indicate continued rapid growth of the human populations in these five primate range regions, with Africa surpassing all the other regions and totaling ca 4bn people by the year 2100. Socioeconomic indicators show that, compared to developed nations, most primate range countries are characterized by high levels of poverty and income inequality, low human development, low food security, high levels of corruption and weak governance. Models of Shared Socioeconomic Pathway scenarios (SSPs) projected to 2050 and 2100 showed that whereas practices of increasing inequality (SSP4) or unconstrained growth in economic output and energy use (SSP5) are projected to have dire consequences for human well-being and primate survivorship, practices of sustainability-focused growth and equality (SSP1) are expected to have a positive effect on maintaining biodiversity, protecting environments, and improving the human condition. These results stress that improving the well-being, health, and security of the current and future human populations in primate range countries are of paramount importance if we are to move forward with effective policies to protect the world’s primate species and promote biodiversity conservation.
Keywords: Primates; Biodiversity; Tropical deforestation; Human development; Poverty; Food security; Corruption; Governance; Civil unrest; Human population growth